1990
DOI: 10.7863/jum.1990.9.5.291
|View full text |Cite
|
Sign up to set email alerts
|

The value of ultrasound for the diagnosis of malignant hyperthermia.

Abstract: A highly feared complication of anesthesia is malignant hyperthermia (MH). In vivo identification of MH is achieved sonographically. Transducers of 7.5 and 5 MHz were used for transverse cuts of the upper and lower leg. Sonographic changes were found in 22 out of 33 subjects from 12 families affected by MH, including several positive subjects not previously known to be subject to MH. The ultrasound image reveals increased parenchymal echogenicity, with obscuring of intramuscular septum and fascia. Myosonograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Previous studies on muscle ultrasound in MH susceptible individuals have reported mixed results. Increased echogenicity in muscles of the lower extremities has been reported using a qualitative approach [ 43 ], however, this could not be reproduced [ 44 ]. Nevertheless, both studies were designed to study the usefulness of muscle ultrasound as a non-invasive test to diagnose MH susceptibility and did not use a quantitative analysis, a broad screening protocol, nor take neuromuscular symptoms into account.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on muscle ultrasound in MH susceptible individuals have reported mixed results. Increased echogenicity in muscles of the lower extremities has been reported using a qualitative approach [ 43 ], however, this could not be reproduced [ 44 ]. Nevertheless, both studies were designed to study the usefulness of muscle ultrasound as a non-invasive test to diagnose MH susceptibility and did not use a quantitative analysis, a broad screening protocol, nor take neuromuscular symptoms into account.…”
Section: Discussionmentioning
confidence: 99%
“…A heterogeneous and grainy pattern of the muscles, with a hypoechoic pattern of the septa and fascia is described by some [3], not by others [4]. The rarity of this syndrome in our ICU has until now prevented us from making an opinion.…”
Section: Malignant Hyperthermiamentioning
confidence: 96%
“…dent specificity and sensitivity. A recent report indicated that ultrasonography could differentiate MH· susceptible patients from normal controls, 2 primarily on the basis of increased echogenicity and decreased definition of fascial planes. We believed that this study design was somewhat weak, as (1) the diagnosis of MH susceptibility was not well documented in some patients, (2) no mention is made if the sanagraphic technique was standardized, and (3) interpretation did not appear to be blinded.…”
mentioning
confidence: 99%